Cathodic biofilm activates electrode surface and achieves efficient autotrophic sulfate reduction. (20th September 2016) - Pozo, Guillermo; Jourdin, Ludovic; Lu, Yang; Keller, Jürg; Ledezma, Pablo; Freguia, Stefano
Abstract: Recent evidence suggests that autotrophic sulfate reduction could be driven by direct and indirect electron transfer mechanisms in bioelectrochemical systems. However, much uncertainty still exists about the electron fluxes from the electrode to the final electron acceptor sulfate during autotrophic sulfate reduction. In this study, linear sweep voltammetry and chronamperometry coupled to off-gas measurement demonstrates that autotrophic sulfate reduction (0.9 ± 0.1 mol SO4 2− -S m −2 d −1 ) is driven by electron fluxes from the cathode to sulfate via hydrogen as intermediate, with 95 ± 0.04% Coulombic efficiency towards sulfide production. Moreover, the biofilm-forming sulfate-reducing bacteria (SRBs) enriched on the cathode showed the remarkable ability to consume hydrogen at a rate of 3.9 ± 0.5 mol H2 m −2 d −1, outcompeting methanogens and homoacetogens for the hydrogen without the need to add chemical inhibitors. Furthermore, quantitative DAIME-FISH of the microbial communities in z-stack images confirmed that SRBs were more abundant (46.1 ± 3.9%) across the 16 ± 2 μm-thick biofilm than Methanobacteriales (13.9 ± 1.8%) and other bacteria (24.8 ± 2.6%) were. Finally, exposing the biofilm to biocidal conditions (pH 3.0, air drying and autoclaving) led to a 27% reduction of the hydrogen production rate, which was nevertheless 5.3 times higher than a bare electrode. Energy dispersive x-ray spectroscopy (EDS) and protein electrode surface analyses revealed the presence of metallic and proteinaceous materials deposited on the surface after biocidal conditions, suggesting that the biofilm was able to modify the electrode surface towards more efficient hydrogen evolution reaction (HER).